Virtual Learning Environment (VLE) implementation strategy: An analysis of practicality for google classroom implementation in Malaysian schools - Awang, Hapini; Mat Aji, Zahurin; Sheik Osman, Wan Rozaini; Abdul Nasir, Aidayani; Mat Deli, Mazzlida; Wan Hamat, Wan Yusof (@JERiS, 2019)
The existing VLE literature has been widespread with considerable debate on the antecedent factors that influence its continuous usage.However, past researchers have not transacted this issue in much detail. What is not yet clear is neither the solution nor strategy to promote VLE sustainable usage. This indicates imbalance attention given to the problem and its treatment. Therefore, this article proposes a VLE implementation strategy as a guideline to implement Google Classroom in Malaysian schools. The implementation strategy was develop based on VLE Success Model and has been endorsed by an expert in educational policy and planning. To validate its practicality, this guideline was reviewed by 14 field experts. The descriptive (quantitative) and content (qualitative) analyses have confirmed the suitability of the VLE implementation strategy to be applied for Google Classroom. However, since it only proposed some of the most important elements to be included in the VLE strategic plan, its applicability in Malaysian schools is subject to their requirements, available resources and other unique characteristics.